2017
DOI: 10.3389/fcvm.2017.00077
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles in Atherosclerosis and Angiogenesis: From Bench to Bedside and Reverse

Abstract: Atherosclerosis (AT) is a progressive chronic disease involving lipid accumulation, fibrosis, and inflammation in medium and large-sized arteries, and it is the main cause of cardiovascular disease (CVD). AT is caused by dyslipidemia and mediated by both innate and adaptive immune responses. Despite lipid-lowering drugs have shown to decrease the risk of cardiovascular events (CVEs), there is a significant burden of AT-related morbidity and mortality. Identification of subjects at increased risk for CVE as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 268 publications
1
56
1
Order By: Relevance
“…Here, we suggest NT-proBNP as a candidate biomarker for risk prediction in patients with CAD, as part of a risk prediction panel including additional biomarkers. Microvesicles, which are small extracellular membrane particles shed by activated and apoptotic cells, have emerged as promising biomarkers for risk prediction not only in many inflammation-associated disorders in general but especially in cardiovascular diseases [24,25]. Although specific roles of each phenotype still remain to be further evaluated, a multipanel approach including NT-proBNP might facilitate risk prediction in CAD patients [26].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Here, we suggest NT-proBNP as a candidate biomarker for risk prediction in patients with CAD, as part of a risk prediction panel including additional biomarkers. Microvesicles, which are small extracellular membrane particles shed by activated and apoptotic cells, have emerged as promising biomarkers for risk prediction not only in many inflammation-associated disorders in general but especially in cardiovascular diseases [24,25]. Although specific roles of each phenotype still remain to be further evaluated, a multipanel approach including NT-proBNP might facilitate risk prediction in CAD patients [26].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Indeed, patients with stable carotid plaques, manifest ischemic stroke and myocardial infarction, all exhibit elevated levels of PMVs [132][133][134]. This indicates that endothelial damage is a key cause for PMV mobilization and it has been suggested that activated PMVs seem to play an important role in thrombus formation and in the pathogenesis of atherosclerosis [135].…”
Section: Platelet Derived Microvesiclesmentioning
confidence: 99%
“…More recent investigations have suggested an additional excessive inflammatory response in the subintimal arterial space followed by thrombus formation [2,3]. Furthermore, several studies have found that blood microparticle levels are elevated in individuals with CAD [4,5]. Different molecules on the surface of the microparticles mediate procoagulant properties that may lead to an acute coronary event [6].…”
Section: Introductionmentioning
confidence: 99%